Тенденции построения источников вторичного электропитания - Левинзон, С.В.; Керцман, С.А. (Технология и конструирование в электронной аппаратуре, 2000)
Совместные действия по развитию базовых стандартных модулей позволят в короткие сроки заполнить формирующийся рынок специальных ИВЭП. The construction's techniques of secondary power sources (SPS) are considered. Comparison technical characteristicses for mains SPS of different power, different manufacturers low-power encapsulated SPS, portable average power, dc voltage converter, as well as low-voltage modules characteristicses are presented.